A preliminary study of Gelidium capense in culture - Bentley, Joanne (Department of Biological Sciences, 2017)
Some preliminary investigations of the effects of temperature, light intensity, salinity and to a lesser extent, water movement, were performed under controlled laboratory culture conditions on the subtidal red alga Gelidium capense, with regards to its potential for aquaculture for its use in the agar and paper-making industries. Agar was also extracted from a wild population and its concentration measured. Four temperature conditions {l0°C, 15°C, 20°c and 25°C) and three salinities (35ppt, 18ppt and 9ppt) were tested as well as four irradiances (120-140 μmol photons m⁻²s⁻¹ , 80-100 μmol photons m⁻²s⁻¹, 60-70 μmol photons m⁻²s⁻¹ and 30-50 μmol photons m⁻²s⁻¹). Water movement was achieved either through aeration or using a flask shaker. A combination of full salinity {35ppt) and 15°C temperature with a light intensity of 80- 100 μmol photons m⁻²s⁻¹ yielded the most optimal growth rates (5 .07% day⁻¹) while poor growth rates (- 1.61% day⁻¹) were observed for the 18ppt and 9ppt salinities and the lowest light intensities. Interestingly, G. capense did not thrive at 20°c or 25°C and instead discoloured rapidly, showed necrosis within a few days, which is in contrast to the findings of most studies focussed on other species of Gelidium under similar conditions. Slow growth rates were achieved at 10°c. The mean agar yield measured ten percent (9.66% ± 1.81) of dry algal weight which is less than a third of the agar yields of some other species of Gelidium and Graci/aria. This suggests that this species may not be as valuable as other Gelidium species in terms of its agar content. It does, however, have high rhizine content and this may lend it to be beneficial in the papermaking industry.